Thermal effects on aquifer storage and recovery in brackish aquifers - Hongkai Li; Zhilin Guo; Zidong Pan; Yang Zhan; Sichen Wan; Hua Zhong; Chunhui Lu; Chunmiao Zheng (Journal of Hydrology, 2026)

Retraction notice to “Investigating the causes of yolk mudding during storage of salted eggs: Water migration accelerates protein and lipid oxidation” [Food Chem. 481 (2025) 144112] - Jiyu Zhang; Songyi Lin; Sichen Lu; Xunze Yuan; Yue Tang; Zhijie Bao (Food Chemistry, 2026)

Phase diagram engineering advances the thermoelectric performance of Zintl phase EuZn2Sb2 - Baopeng Ma; Honghao Yao; Shanghao Chen; Xiaofang Li; Shiquan Lu; Wenhua Xue; Tianyu Zhang; Linmao Wen; Sichen Duan; Yunzi Ren; Yumei Wang; Feng Cao; et al. (Chemical Engineering Journal, 2026)

Regulatory mechanisms of adipocyte differentiation and fat deposition in pigs: Implications for meat quality improvement - Wenjing Wu; Xiao Cheng; Lu Shen; Shenpeng Zheng; Jie Zhang; Keke Liu; Sichen Yang; Xinrong Lian; Jin Zhang (Food Bioscience, 2026)

Ground software architecture for a lunar particle detector: Implementation with a double-sided silicon strip detector - Thanayuth Panyalert; Shariff Manuthasna; Peerapong Torteeka; Xu He; Ning Zhang; Jianing Zheng; Bin Zhang; Dong Yang; Haibo Yang; Jingtian Xian; Yiwei Bao; Sichen Lu; et al. (Advances in Space Research, 2026)

Non-invasive assessment of the visual environment using conditional generative adversarial networks - Sichen Lu; Dongjun Mah; Athanasios Tzempelikos (Building and Environment, 2026)

Toward AI-assisted, human-centered daylighting operation: Non-invasive daylighting preference evaluation using deep learning - Sichen Lu; Dongjun Mah; Athanasios Tzempelikos (Building and Environment, 2026)

Uncovering the potential of rosmarinic acid as a natural antimicrobial agent: effective inhibition of growth and biofilm formation in Bacillus cereus - Lu Tian; Qi Qi; Sichen Liao; Guoli Gong; Zhenbin Liu; Jiayi Zhang; Hongbo Li; Qing Sun; Haizhen Mo; Liangbin Hu (Food Control, 2025)

RETRACTED: Investigating the causes of yolk mudding during storage of salted eggs: Water migration accelerates protein and lipid oxidation - Jiyu Zhang; Songyi Lin; Sichen Lu; Xunze Yuan; Yue Tang; Zhijie Bao (Food Chemistry, 2025)

Glare-based selection of roller shade properties - Sichen Lu; Taoning Wang; Athanasios Tzempelikos (Building and Environment, 2024)

Antimicrobial mechanism of morusin against Bacillus cereus and its potential as an antimicrobial agent - Sichen Liao; Guoli Gong; Jiapeng Fu; Jie Wang; Qi Qi; Lemei Hu; Chang Gao; Minmin Wang; Haoyue Cui; Jiaqiang Liu; Lu Tian (Food Bioscience, 2024)

Key biological processes and essential genes for Proteus mirabilis biofilm development inhibition by protocatechuic acid - Lu Tian; Chang Gao; Jiaxing Lu; Sichen Liao; Guoli Gong (International Journal of Food Microbiology, 2024)

Environmental impact assessment of multi-source solid waste based on a life cycle assessment, principal component analysis, and random forest algorithm - Sichen Chen; Lu Yu; Chenmu Zhang; Yufeng Wu; Tianyou Li (Journal of Environmental Management, 2023)

Effects of Mud Supply and Hydrodynamic Conditions on the Sedimentary Distribution of Estuaries: Insights from Sediment Dynamic Numerical Simulation - Qian Zhang; Mingming Tang; Shuangfang Lu; Xueping Liu; Sichen Xiong (Journal of Marine Science and Engineering, 2023)
Estuaries are important sediment facies in the fluvial-to-marine transition zone, are strongly controlled by dynamic interactions of tides, waves, and fluvial flows, and show various changes in depositional processes and sediment distribution. Deep investigations on the sediment dynamic processes of the sand component of estuaries have been conducted; however, the understanding of how mud supply affects estuaries’ sedimentary characteristics and morphology is still in vague. Herein, the effects of mud concentration, mud transport properties, fluvial discharge, and tidal amplitude on the sedimentary characteristics of an estuary were systematically analyzed using sedimentary dynamic numerical simulation. The results show that the mud concentration has significant effects on the morphology of tidal channels in estuaries, which become more braided with a lower mud concentration, and straighter, with reduced channel migration, with a higher mud concentration. The mud transport properties, namely, setting velocity, critical bed shear stress for sedimentation, and erosion, mostly affect the ratio between the length and width (RLW) of the sand bar; a sheet-like sand bar with a lower RLW value develops in the lower settling velocity, while there are obvious strip shaped bars with a high RLW value in the higher settling velocity case. Moreover, the effects of hydrodynamic conditions on sedimentary distribution were analyzed by changing the tidal amplitudes and fluvial discharges. The results show that a higher tidal amplitude is often accompanied by a stronger tidal energy, which induces a more obvious seaward progradation, while a higher fluvial discharge usually yields a higher deposition rate and yields a greater deposition thickness. From the above numerical simulations, the statistical characteristics of tidal bars and mud interlayers were further obtained, which show good agreement with modern sedimentary characteristics. This study suggests that sedimentary dynamic numerical simulation can provide insights into an efficient quantitative method for analyzing the effects of mud components on the sediment processes of estuaries.